2006
DOI: 10.1021/jp061698r
|View full text |Cite
|
Sign up to set email alerts
|

New Type of Phase Transformation in Gas Hydrate Forming System at High Pressures. Some Experimental and Computational Investigations of Clathrate Hydrates Formed in the SF6−H2O System

Abstract: In this work, we present a new, previously unknown type of structure transformation in the high-pressure gas hydrates, which is related to the existence of two different isostructural phases of the sulfur hexafluoride clathrate hydrates. Each of these phases has its own stability field on the phase diagram. The difference between these hydrates consists of partial filling of small D cages by SF(6) molecules in the high-pressure phase; at 900 MPa, about half of small cages are occupied. Our calculations indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…The conformational search of the peptides has been performed within MulgiGen algorithm using combined MM3/ MERA force field with continual account of solvent (Potemkin et al, 2002;Aladko et al, 2006). Calculation of surface has been made according to Connolly algorithm (Connolly, 1983(Connolly, , 1985.…”
Section: Methodsmentioning
confidence: 99%
“…The conformational search of the peptides has been performed within MulgiGen algorithm using combined MM3/ MERA force field with continual account of solvent (Potemkin et al, 2002;Aladko et al, 2006). Calculation of surface has been made according to Connolly algorithm (Connolly, 1983(Connolly, , 1985.…”
Section: Methodsmentioning
confidence: 99%
“…Manakov et al have found two new hydrates in the THF-water system above 0.25 and 0.49 GPa, respectively, and dissociation into THF and water at 3 GPa, 67 but there is to date no structural characterisation. Aladko et al 68 and Dyadin et al 69 have studied the dissociation curve of the SF 6 -water system using DTA and found evidence for two new hydrates. Using X-ray diffraction techniques, they showed that the first transition at 0.05 GPa is a change from CS-II to CS-I.…”
Section: Other Simple Molecular Hydratesmentioning
confidence: 99%
“…The second transition at 0.13 GPa is isostructural and involves population of the small cage with guest species, as shown by neutron diffraction studies at 0.9 GPa. 68,69 Based on Raman data they argued that no further structural transitions occur at higher pressures but found evidence for dissociation into ice and SF 6 at 4.4 GPa. 68,69 There has also been work on these hydrates at low temperatures (77 K).…”
Section: Other Simple Molecular Hydratesmentioning
confidence: 99%
“…[59] Under these conditions, a weak effect of the nature of guest molecule on compressibility (bulk modulus) of the gas hydrate appears to be reasonable. On the other hand, in the case of the high-pressure hydrate of SF 6 (CS-I) [60,61] and the hydrate of CCl 4 (CS-II) existing at atmospheric pressure, [62] guest molecules are in close contact with the atoms of the framework or with the guest molecules occupying neighboring cavities. In these cases, one may expect substantially smaller hydrate compressibilities in comparison with the values given above.…”
mentioning
confidence: 99%
“…In these cases, one may expect substantially smaller hydrate compressibilities in comparison with the values given above. Data available on the hydrate of SF 6 (CS-I) [60] show that the compression curve is not described by Equation (2); in this situation, the slope of the compression curve to the pressure axis rapidly decreases as the pressure increase.…”
mentioning
confidence: 99%